2013
DOI: 10.1038/npp.2013.120
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein Inhibition Increases the Brain Distribution and Antidepressant-Like Activity of Escitalopram in Rodents

Abstract: Despite the clinical prevalence of the antidepressant escitalopram, over 30% of escitalopram-treated patients fail to respond to treatment. Recent gene association studies have highlighted a potential link between the drug efflux transporter P-glycoprotein (P-gp) and response to escitalopram. The present studies investigated pharmacokinetic and pharmacodynamic interactions between P-gp and escitalopram. In vitro bidirectional transport studies revealed that escitalopram is a transported substrate of human P-gp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 46 publications
5
43
4
Order By: Relevance
“…However, to our knowledge, there were no data pertaining to human P-gp available for mirtazapine before the present study. In contrast, two studies have reported pharmacogenetic associations between ABCB1 SNPs and response to the SSRI escitalopram (Lin et al, 2011;Singh et al, 2012), and we have recently identified escitalopram as a transported substrate of human P-gp in the same in vitro model as used in the present study (O'Brien et al, 2013). In addition, the finding that amitriptyline, duloxetine and fluoxetine were not transported substrates of human P-gp in our in vitro bidirectional transport model may help to explain why no association was found between ABCB1 SNPs and response to these antidepressants in previous clinical studies (Roberts et al, 2002;Laika et al, 2006;Perlis et al, 2010).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, to our knowledge, there were no data pertaining to human P-gp available for mirtazapine before the present study. In contrast, two studies have reported pharmacogenetic associations between ABCB1 SNPs and response to the SSRI escitalopram (Lin et al, 2011;Singh et al, 2012), and we have recently identified escitalopram as a transported substrate of human P-gp in the same in vitro model as used in the present study (O'Brien et al, 2013). In addition, the finding that amitriptyline, duloxetine and fluoxetine were not transported substrates of human P-gp in our in vitro bidirectional transport model may help to explain why no association was found between ABCB1 SNPs and response to these antidepressants in previous clinical studies (Roberts et al, 2002;Laika et al, 2006;Perlis et al, 2010).…”
Section: Discussioncontrasting
confidence: 55%
“…In light of well-documented species differences in P-gp activity and substrate specificity (Yamazaki et al, 2001;Katoh et al, 2006;Baltes et al, 2007;Syvanen et al, 2009), it was vital that further experiments to confirm that mirtazapine is not a transported substrate of human P-gp be conducted to facilitate informed interpretation of these clinical studies. Moreover, we have also demonstrated that inhibition of P-gp enhances the brain distribution and antidepressant-like activity of escitalopram in rodents (O'Brien et al, 2013). In contrast, two studies have reported pharmacogenetic associations between ABCB1 SNPs and response to the SSRI escitalopram (Lin et al, 2011;Singh et al, 2012), and we have recently identified escitalopram as a transported substrate of human P-gp in the same in vitro model as used in the present study (O'Brien et al, 2013).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In this study, we investigate the effect of oat3 inhibition, which represents a novel potential augmentation strategy, on brain levels of bumetanide. Previously, studies in our group and others have demonstrated the potential of efflux transporter inhibition at the BBB to increase brain levels of neuropsychopharmacological agents [36,37]. OAT3 can be inhibited by probenecid, penicillins and statins [31,38,39].…”
Section: Introductionmentioning
confidence: 97%
“…K p,uu,brain of escitalopram is also lower than 0.1 without pretreatment of CSA, yet increase, (but below 0.33) with P-gp inhibition [86]. These microdialysis studies [16,81] suggest that for K p,uu,brain values determined by this method, the cut-off between BBB+ and BBB− may be even lower than 0.1.…”
Section: Reliability Of Methods To Evaluate Brain Penetration Of Amentioning
confidence: 99%